2022
DOI: 10.4102/jamba.v14i1.1088
|View full text |Cite
|
Sign up to set email alerts
|

Inter-agency collaboration and disaster management: A case study of the 2005 earthquake disaster in Pakistan

Abstract: In post disastrous situations, coordinated and integrated interventions aimed at relief and rehabilitation not only help facilitate reaching out to the affected communities in a timely fashion but also pave the way to channel scarce and valued resources towards end users in an efficient and effective manner. This article attempts to trace the origins and gradual development of ‘inter-agency collaboration’ and the implications thereof for disaster management strategies in Pakistan through an analysis of relief … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This conclusion is backed by studies that analyzed how leadership styles affected collaboration in environment management [ 134 ]. Earlier empirical research on collaborative administration and managerial leadership is reported not only from Pakistan but also from other countries [ 135 , 136 ]. In addition, prior empirical research has demonstrated that PL effects civil servants commitment, workplace engagement, performance, citizenship behaviour and change orientations [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is backed by studies that analyzed how leadership styles affected collaboration in environment management [ 134 ]. Earlier empirical research on collaborative administration and managerial leadership is reported not only from Pakistan but also from other countries [ 135 , 136 ]. In addition, prior empirical research has demonstrated that PL effects civil servants commitment, workplace engagement, performance, citizenship behaviour and change orientations [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is backed by studies that analyzed how leadership styles affected collaborative administration [138]. Earlier empirical research on collaborative administration and managerial leadership is reported not only from Pakistan but also from other countries [139,140]. In addition, prior empirical research has demonstrated that PL enhances the attitudes and behaviours of civil servants, including their commitment, engagement, health performance, citizenship behaviour, and change orientations [29].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate equipment allows them to search, evacuate, and provide medical assistance more effectively and efficiently [10]. (3) The TNI-AU SAR team personnel cooperate with other related parties, such as the Regional Disaster Management Agency (BPBD), the police, and local government agencies. Good coordination between the Indonesian Air Force SAR team and related parties allows them to support each other, share information, and utilize resources effectively.…”
Section: Tni-au Sarmentioning
confidence: 99%
“…Through a comprehensive approach, this research will identify factors that influence collaboration, such as coordination, exchange of information, and effective division of tasks. The results of this study can provide insight into the importance of good collaboration and provide recommendations for increasing inter-agency cooperation in earthquake emergency response [3]. This research will examine how the personnel of the Indonesian Air Force SAR team monitor the latest information that is relevant to the earthquake emergency response situation.…”
mentioning
confidence: 99%